Serologic and molecular survey for hepatitis E virus in wild boar (Sus scrofa) in Central Italy. (September 2015) - Mazzei, M.; Nardini, R.; Verin, R.; Forzan, M.; Poli, A.; Tolari, F.
Abstract: The aim of this study was to further investigate the role of wild boar ( Sus scrofa ) as a reservoir for hepatitis E virus (HEV). Sixty-four blood and faecal samples collected from wild boar hunted in Central Italy in 2011–2012 were examined by indirect enzyme-linked immunosorbent assay and RT-PCR analysis. Positive RT-PCR samples were further examined by nucleotide sequence determination and subsequent phylogenetic analysis. Thirty-six sera (56.2%) were positive for HEV-specific antibodies, and six (9.4%) faecal samples scored RT-PCR-positive results. Four animals were positive by both enzyme-linked immunosorbent assay and RT-PCR. Phylogenetic analysis showed that the detected wild boar–derived HEV sequences clustered within genotype 3, with similarity to sequences of human origin collected in a nearby area in 2012. Our data confirm that HEV is endemic in the wild boar population in the research area and that these wild animals could play an important role in the epidemiology of HEV infection.